Reliability and validity of a new maximal anaerobic shuttle running test - Dardouri, W.; Gharbi, Z.; Selmi, M. A.; Sassi, R. H.; Moalla, W.; Chamari, K.; Souissi, N. (International Journal of Sports Medicine, 2014)
The purpose of this study was twofold: first to assess the relative and absolute reliability of a new Maximal Anaerobic Shuttle Running Test (MASRT), and second to evaluate the criterion validity of the MASRT. 16 team sport players participated in this study. The velocity (VMASRT) and the number of shuttles achieved at volitional exhaustion were measured. To assess the reliability of the MASRT, each player performed the MASRT twice, on separate days. The criterion validity of the MASRT was determined by examining the relationship between MASRT indices and the Wingate test (WingT) performances. Results showed no difference between test-retest MASRT scores for VMASRT and the number of shuttles (P>0.05). The intraclass correlation coefficients (ICC) values for VMASRT and Shuttle number were 0.84 and 0.80, respectively. The coefficients of variation (CV) and the mean difference (bias)±the 95% limits of agreement for the same variables were 3.6 and 12.9%, and 0.02±0.37m/s and 0.3±6.7, respectively. The strongest correlation was found between mean power output relative to body mass (MPO) measured during the WingT and VMASRT (r=0.77, P<0.001). The MASRT constitutes a reliable and valid field tool for assessing short term repeated running capacity of team sport players.